Abschreiben - ein Problem in mathematischen Lehrveranstaltungen? - Liebendörfer, Michael; Göller, Robin (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014 Beiträge zum gleichnamigen Symposium am 7. & 8. November 2014 an der Westfälischen Wilhelms-Universität Münster)

Eine alternative Einstiegsvorlesung in die Fachmathematik – Konzept und Auswirkungen - Göller, Robin; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2016)
Keywords: _tablet; Abschreiben

Abschreiben von Übungsaufgaben in traditionellen und innovativen Mathematikvorlesungen - Liebendörfer, Michael; Göller, Robin (Mitteilungen der Deutschen Mathematiker-Vereinigung)
Keywords: _tablet; Abschreiben

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Gräler, Manuel; Henke, Christian; Molo, Mirko Hessel-von; Dellnitz, Michael; Trächtler, Ansgar (Procedia Technology)
In a wide range of applications, it is desirable to optimally control a system with respect to concurrent, potentially competing goals. This gives rise to a multiobjective optimal control problem where, instead of computing a single optimal solution, the set of optimal compromises, the so-called Pareto set, has to be approximated. When it is not possible to compute the entire control trajectory in advance, for instance due to uncertainties or unforeseeable events, model predictive control methods can be applied to control the system during operation in real time. In this article, we present an algorithm for the solution of multiobjective model predictive control problems. In an offline scenario, it can be used to compute the entire set of optimal compromises whereas in a real time scenario, one optimal compromise is computed according to an operator's preference. The results are illustrated using the example of an industrial laundry. A logistics model of the laundry is developed and then utilized in the optimization routine. Results are presented for an offline as well as an online scenario.

Monitoring and debugging using an SDK for NFV-powered telecom applications - v. Rossem, S.; Tavernier, W.; Peuster, Manuel; Colle, D.; Pickavet, M.; Demeester, P. (Proc. IEEE Conference on Network Function Virtualization and Software Defined Network (NFV-SDN), Demo Track)

Wave interaction in photonic integrated circuits: Hybrid analytical / numerical coupled mode modeling - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XX)
Typical optical integrated circuits combine elements, like straight and curved waveguides, or cavities, the simulation and design of which is well established through numerical eigenproblem-solvers. It remains to predict the interaction of these modes. We address this task by a ”Hybrid” variant (HCMT) of Coupled Mode Theory. Using methods from finite-element numerics, the optical properties of a circuit are approximated by superpositions of eigen-solutions for its constituents, leading to quantitative, low-dimensional, and interpretable models in the frequency domain. Spectral scans are complemented by the direct computation of supermode properties (spectral positions and linewidths, coupling-induced phase shifts). This contribution outlines the theoretical background, and discusses briefly limitations and implementational details, with the help of an example of a 2-D coupled-resonator-optical-waveguide configuration.
Keywords: tet_topic_waveguide; tet_topic_numerics

Boomerang: Demand-Driven Flow- and Context-Sensitive Pointer Analysis for Java - Späth, Johannes; Nguyen Quang Do, Lisa; Ali, Karim; Bodden, Eric (European Conference on Object-Oriented Programming (ECOOP))
Keywords: ATTRACT; ITSECWEBSITE

Parallelisierung von Algorithmen zur IR-Luftbildanalyse von Laubholzmischbeständen zur Verifizierung der Ausbreitung von Eichenkomplexschäden - Bülling, Jonas

Price-Based Allocation Games - Koepe, Jörn

Sicherheit von hybriden FPGA-Systemen in der industriellen Automatisierungstechnik -- Anforderungen und Umsetzung - Tölke, Christian